Meningkatkan Kompetensi Guru dalam Penyusunan Perangkat Pembelajaran Berbasis Blendend Learning melalui Supervisi Kepala Sekolah pada Masa Pandemi Covid-19 di SDN 1 Langkapura Bandar Lampung - Kusrina, Kusrina (STKIP PGRI Bandar Lampung, 2022)
Inter-class visit technique is an activity carried out by one teacher visiting another class in the school environment itself. This inter-class visit can be done individually between teachers or a group of teachers visit a teacher. Through these inter-class visits, it is hoped that teachers will gain new experiences from their more professional peers. Best Practice with the subject of teachers at SD Negeri 1 Langkapura Bandar Lampung City totaling 31 people. This research was carried out in two action cycles with 2 meetings in each cycle. The results showed an increase in the ability of teachers to use learning media where in cycle 1, meeting 1 was 60% in the sufficient category, increased at meeting 2 to 67% in the good category. In the second cycle, meeting 1 increased to 75% in the good category and there was an increase in the second meeting to 85% in the very good category. Implementation of supervision with interclass visits technique in cycle I meeting 1 was 64% with good category increasing to 76% with good category at meeting 2, In cycle 2 meeting 1 increased again to 81% with very good category and at meeting 2 to 88% with very good category.